Paradigm shifts in critical care medicine: the progress we have made. (December 2015) - Vincent, Jean-Louis; Creteur, Jacques
Abstract There have really been no single, major, advances in critical care medicine since the specialty came into existence. There has, however, been a gradual, continuous improvement in the process of care over the years, which has resulted in improved patient outcomes. Here, we will highlight just a few of the paradigm shifts we have seen in processes of critical care, including the move from small, closed units to larger, more open ICUs; from a paternal "dictatorship" to more "democratic" team-work; from intermittent to continuous, invasive to less-invasive monitoring; from "more" interventions to "less" thus reducing iatrogenicity; from consideration of critical illness as a single event to realization that it is just one part of a trajectory; and from "four walls" to "no walls" as we take intensive care outside the physical ICU. These and other paradigm shifts have resulted in improvements in the whole approach to patient management, leading to more holistic, humane care for patients and their families. As critical care medicine continues to develop, further paradigm shifts in processes of care are inevitable and must be embraced if we are to continue to provide the best possible care for all critically ill patients.